Effect of the plasma density scale length on the direction of fast electrons in relativistic laser-solid interactions - Santala, M; Zepf, M; Watts, I; Beg, F; Clark, E; Tatarakis, M; Krushelnick, K; Dangor, A; McCanny, T; Spencer, I; Singhal, R; Ledingham, K; et al. (2000)
The angular distribution of bremsstrahlung gamma rays produced by fast electrons accelerated in relativistic laser-solid interaction has been studied by photoneutron activation in copper. We show that the gamma-ray beam moves from the target normal to the direction of the k(laser) vector as the scale length is increased. Similar behavior is found also in 2D particle-in-cell simulations.